A synopsis of the multilocular species of Ixora (Rubiaceae) from Madagascar - de Block, Petra (Phytotaxa, 2014)
Two new Ixora species from Madagascar are described, Ixora lagenifructa and I. quadrilocularis. Ixora littoralis, previously positioned in the monospecific genus Thouarsiora, is newly named I. homolleae. These three species are characterized by 4-locular ovaries and fruits, 4-lobed stigmas, large fruits with thick walls and well-developed calyces. A fourth species, I. trimera, shows the same characters but its ovaries are 2-, 3- or 4-locular and its stigmas are 2-, 3- or 4-lobed. A dichotomous key, detailed descriptions and distribution maps are given for these four species, the only multilocular ones in Madagascar.